Common ABCA4 mutations in South Africans: frequencies, pathogenicity and genotype-phenotype correlations - Nossek, C (Division of Human Genetics, 2014)
Stargardt disease (STGD), a juvenile-onset form of macular dystrophy resulting in a severe reduction of central vision, may be inherited in either an autosomal recessive or autosomal dominant manner. To date the only gene found to be involved with the autosomal recessive form is ABCA4. Mutations in this gene are associated not only with STGD, but with other autosomal recessive retinal diseases. Due to the numerous mutations detected in ABCA4 and their associated phenotypic heterogeneity, a genotype-phenotype model has been proposed based on the amount of ABCA4 protein activity. Research in the Division of Human Genetics at the University of Cape Town (UCT) has suggested possible ABCA4 founder mutations underlying STGD in the South African Caucasian Afrikaner population and has identified seven (C1490Y, R602W, IVS38-10T>C, L2027F, V256V, G863A, and R152X) common mutations. In a cohort of patients affected with an ABCA4-associated retinopathy (AAR) a total of 36% were identified as having various bi-allelic combinations of the seven mutations.In the current study, SNaPshot PCR, allele-specific PCR (AS-PCR) and denaturing high performance liquid chromatography (dHPLC) analysis were used to screen for the seven mutations in a patient cohort and a control cohort. A high detection rate of bi-allelic disease-causing mutations in total of 28/72 patients (i.e. 38.89% were fully characterised) confirmed the designed assay to be a viable screening tool, which could be employed in a diagnostic setting. The detection of 12 heterozygotes in the Caucasian control samples (n = 269; 169 of which were specifically Afrikaner) resulted in an estimated background frequency of 4.46 per 100 individuals. This could be used by counsellors to discuss carrier risks with patients and their family members. Bioinformatic tools (PolyPhen, SIFT, PMUT, PANTHER PSEC, ESEfinder, and the BDGP Splice Site Prediction programme) revealed the predicted pathogenicity of the seven mutations to be as follows (in order of decreasing pathogenicity): C1490Y, R602W, V256V, R152X, G863A, L2027F, and IVS38-10T>C. Statistical analysis (using the Kruskal-Wallis test and the Wilcoxon Rank Sum test) showed no significant12effect of mutation combination on phenotype (i.e. AOO/severity as a measure of clinical outcome).To improve the understanding of the genotype-phenotype correlation a larger cohort of South African STGD patients with the same common mutations in various combinations and the availability of sufficient clinical data, is required. Further investigations into the genotype-phenotype correlation, combined with the information on the pathogenicity of the mutations, could result in increased understanding regarding the impact of each mutation, thus enhancing the clinical utility of identifying ABCA4 mutations.